PENGARUH KOMUNIKASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA LEMBAGA SMART FAST GLOBAL EDUCATION PEKANBARU - Husni Fuaddi; Rafika Amenda (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to determine the effect of communication on employee work productivity at the Pekanbaru Smart Fast Global Education Institute. The sample in this study were 34 employees of the Smart Fast Global Education Pekanbaru Institute. Analysis of the data used is the validity test, reliability test, normality test simple linear regression, coefficient of determination test and T test. The results of the research are the effect of communication on employee work productivity at the Smart Fast Global Education Pekanbaru Institute which has a significant effect with a determination coefficient value R2 of 0.398 . This means that the work productivity variable (Y) is influenced by the communication variable (X) by 39.8%, while the remaining 60.2% is explained by other factors not examined by the authors. The communication variable (X) has a positive influence on work productivity (Y) with a regression coefficient of 0.790 indicating that if communication increases by 1 unit, the employee productivity variable will increase by 0.311, which means that the higher the communication, the higher the work productivity. The results of the hypothesis test show that the value of t count > t table (4.604 > 1.693) with sig 0.000 < sig 0.05 which means Ho is rejected and Ha is accepted. So it can be concluded that communication has a significant effect on employee work productivity at the Smart Fast Global Education Institute.